Numerical study on the effect of jet spacing on the Swirl flow and heat transfer in the turbine airfoil leading edge region. (1st November 2016) - Liu, Zhao; Li, Jun; Feng, Zhenping; Simon, Terrence
ABSTRACT: In this paper, flow and heat transfer of a swirl chamber that models an internal cooling passage for a gas turbine airfoil leading edge is studied with numerical simulation. The geometry consists of a circular pipe, and rectangular section inlets that lead inlet flow to impinge tangentially on the circular pipe. The effects of the ratio of jet spacing to swirl chamber radius and Reynolds numbers on swirl cooling performance are investigated. The results indicate how the pressure loss and globally averaged Nusselt number on the swirl chamber wall increase with increases of Reynolds number and the ratio of jet spacing to swirl chamber radius. A Nusselt number correlation on these parameters is suggested. Also shown is how Nusselt numbers on the swirl chamber surface increase with the ratio of jet spacing to swirl chamber radius.